Whiteboard selling : empowering sales through visuals - Sommers, Corey (Wiley, 2013)
Create compelling whiteboard presentations to engage your customers and win their business Whiteboard Selling offers a step-by-step approach to transforming your message and selling style by using powerful visual stories that inspire and engage customers and prospects. Free your sales force from relying on slides and other static sales tools during the sales process. Whiteboard Selling offers practical guidance and skills to enable marketing and sales teams to quickly adopt visual story telling practices that apply to today's fast-moving, competitive selling environment.